Misi Utama Tokoh Monster dalam Novel Frankenstein in Baghdad Analisis Semiotika Roland Barthes - Karay Lazuardi Novanka; Zubair Zubair (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2026)
This study aims to examine the semiotic construction and deconstruction of the Monster's main mission in Ahmed Saadawi's novel Frankenstein in Baghdad. Amid the legal vacuum in post-2003 Iraq, the Monster emerges as a justice-seeker, presenting a complex teleological paradox. This research employs a descriptive-analytical qualitative method. Robert Stanton's Structuralism is used to map the character's narrative function, while Roland Barthes' Semiotics is applied to dissect the meaning-making process at the denotative, connotative, and mythical levels. The findings reveal that the Monster's mission undergoes a radical semantic distortion. Initially, it is constructed into a "Savior Myth" as a restorative justice agent, driven by the collective trauma of the society. However, the biological reality of its decaying body deconstructs this sacred mission, forcing the Monster to kill innocent civilians merely to survive. This demythologization process is accelerated by the Sophist's nihilistic rationalization. In discussion, this ideological collapse shifts the savior myth into a "Dystopian Myth" where extreme violence is normalized as a survival mechanism. Ultimately, the Monster's failure to uphold its mission serves as a dark allegory for the failure of the Iraqi national project, which remains trapped in an endless cycle of violence.